Treasure Hunt dalam Pelaksanaan English Camp: Upaya Sistematis Meningkatkan Kompetensi Bahasa Inggris Mahasiswa - Siradjuddin, Suharti; Yahrif, Muhammad; Ahmad; Rais, Anisatun Humayrah (Yayasan Habiburrahman Jamalu Bina Ummat, 2026)
This community service program was implemented through an English Camp integrating a Treasure Hunt activity using a Project Based Learning (PjBL) approach, aimed at improving students’ English competence, particularly speaking ability, communication fluency, and self-confidence. The program was conducted in Malino on 14–16 November 2025 and involved 148 accounting students who were divided into small groups and required to use English throughout all activities. The Treasure Hunt was designed as a collaborative project in which students completed a series of English-based tasks at four different posts, enabling them to experience learning through planning, discussion, teamwork, task completion, and reflective communication in authentic contexts. Data were obtained through direct observation, speaking performance assessment, and participants’ responses. The results indicate significant improvement in students’ confidence to speak, ability to understand English instructions, discipline, teamwork, and learning motivation. Furthermore, the program provided meaningful and authentic learning experiences that differ from formal classroom learning. Therefore, the Treasure-Hunt-Based English Camp with a Project Based Learning approach proved to be an effective and systematic strategy to enhance students’ English competence and is recommended as a sustainable model for strengthening English learning in higher education settings.